2022
DOI: 10.1097/acm.0000000000004993
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Diagnostic Uncertainty at Emergency Department Discharge: A Simulation-Based Mastery Learning Randomized Trial

Abstract: Purpose There are no standardized approaches for communicating with patients discharged from the emergency department with diagnostic uncertainty. This trial tested efficacy of the Uncertainty Communication Education Module, a simulation-based mastery learning curriculum designed to establish competency in communicating diagnostic uncertainty. Method Resident physicians at 2 sites participated in a 2-arm waitlist randomized controlled trial from September 2019 to June 2020. After baseline (T1) assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…These results confirm those of previous studies, which demonstrated the ability of deliberate practice to facilitate the acquisition of expertise in medicine, across domains as varied as communication in the emergency department or intensive care unit, resuscitation, and surgery. [32][33][34][35][36] Efficacy: compliance with clinical practice guidelines for the triage of patients with trauma…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm those of previous studies, which demonstrated the ability of deliberate practice to facilitate the acquisition of expertise in medicine, across domains as varied as communication in the emergency department or intensive care unit, resuscitation, and surgery. [32][33][34][35][36] Efficacy: compliance with clinical practice guidelines for the triage of patients with trauma…”
Section: Discussionmentioning
confidence: 99%
“…These results confirm those of previous studies, which demonstrated the ability of deliberate practice to facilitate the acquisition of expertise in medicine, across domains as varied as communication in the emergency department or intensive care unit, resuscitation, and surgery. 32 , 33 , 34 , 35 , 36 For example, a meta-analytic comparative review of the literature on skill acquisition in procedural domains (eg, laparoscopic surgery) identified a correlation between the use of deliberate practice and positive outcomes ( r = 0.71). 32 Our study expands on these results by focusing on diagnostic reasoning and targeting the performance of physicians in practice rather than medical trainees.…”
Section: Discussionmentioning
confidence: 99%
“…Rather than framing this as a deficiency in clinical skills and something that should never been acknowledged, diagnostic uncertainty of varying degrees should be normalized as an expected occurrence during emergency care 4 . Education and training through the use of validated instruments to scaffold provider conversations with their patients, for example, through the uncertainty communication checklist, has been demonstrated to increase mastery in physicians successfully communicating diagnostic uncertainty to ED patients 5 …”
Section: Future Directions For Diagnostic Safetymentioning
confidence: 99%
“…4 Education and training through the use of validated instruments to scaffold provider conversations with their patients, for example, through the uncertainty communication checklist, has been demonstrated to increase mastery in physicians successfully communicating diagnostic uncertainty to ED patients. 5 In conclusion, the AHRQ report should not be read as an indictment of EM providers but, rather, raise awareness about the need for more effective solutions to address diagnostic error in this unique and high-risk clinical environment that provides acute and unscheduled care. The resulting controversy is best met with a redoubling of efforts and increased support for research examining how we can more effectively identify and reduce diagnostic error across all health care settings and mitigate the associated waste and patient harm.…”
Section: Future Direc Tions For Diag Nos Tic Sa Fe T Ymentioning
confidence: 99%